Maternal metabolic syndrome affects the progeny's redox balance and increases neuroinflammation with neurodevelopmental and metabolic adverse consequences - Prado Spalm, Facundo Heber (2023)
Various lifestyle factors, including diet, can impact on redox balance and brain health. Consumption of fructose-sweetened beverages has drastically increased in the last decades and is widely associated with metabolic disease, systemic proinflammatory status and adverse transgenerational effects. To date, the impact of maternal fructose intake in brain redox balance and function of the offspring is less explored. We investigated whether the progeny of mothers with Metabolic Syndrome (MetS), induced by ad libitum consumption of a 20% fructose solution, present any redox alteration in the brain as a consequence of being gestated in a metabolic altered intrauterine environment. Wistar rats were randomly separated into two groups with access to water or fructose (20% w/v in water) for 10 weeks. After MetS was confirmed, dams were mated with control males and continued drinking water or fructose solution during gestation. At postnatal day (PN) 1, a subgroup of offspring of each sex was sacrificed and brains were dissected for oxidative stress and inflammatory status analysis. The developmental milestones and behavioral test were also evaluated (PN3-PN100) in another subgroup of offspring to identify any long-term consequence to being gestated by a dam with MetS. Maternal MetS affects the redox balance and increases neuroinflammation in female offspring at birth. Sexually dimorphic effects were also found on the progeny's acquisition of neurodevelopmental milestones and in their psychiatric, cognitive and metabolic state. Although direct extrapolation of our findings cannot be made to humans, the results presented herein reinforce the necessity of considering the potentially negative effects of fructose-induced MetS prior to, and during pregnancy in offspring’s brain and metabolic physiology